Review of The Institutional View on The Liberalization and Management of Capital Flows : Background Note on Capital Flows and Capital Flow Management Measures - Benefits and Costs - Pasricha, Gurnain Kaur (Policy Papers; Policy Paper, 2022)
The Fund's Institutional View (IV) recognizes the benefits of and risks associated with capital flows. Since the IV was adopted, a growing literature has provided additional insights into the benefits and risks from capital flows. This note summarizes the insights from the recent literature and the experiences of staff since the adoption of the IV that have informed this review.